1998
DOI: 10.1103/physrevb.58.11386
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in crystalline polyethylene: A chain surrounded by immovable neighbors

Abstract: A numerical solution to the problem of existence and stability of topological solitons in a polyethylene chain surrounded by immovable neighboring chains is obtained. In the framework of a realistic model that takes into account deformations of valence bonds, valence and torsional angles, as well as intermolecular interactions, three types of solitons describing local topological defects in the crystal are found. They correspond, respectively, to ͑i͒ stretching or compression of the zigzag backbone by one latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…We classify the solitons, investigate stability of the solitons with respect to thermal oscillations, interactions between the solitons, interaction of the solitons with inhomogeneities of the chain. To solve all these problems, we use numericalvariation methods efficiency of which was proved in the works [31,32,33,34,35,36], devoted to the analysis of nonlinear dynamics of molecular chains and polymer crystals.…”
Section: Introductionmentioning
confidence: 99%
“…We classify the solitons, investigate stability of the solitons with respect to thermal oscillations, interactions between the solitons, interaction of the solitons with inhomogeneities of the chain. To solve all these problems, we use numericalvariation methods efficiency of which was proved in the works [31,32,33,34,35,36], devoted to the analysis of nonlinear dynamics of molecular chains and polymer crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to consider their accumulation as the initial mechanism in the premelting of the PE crystal. A more detailed description of the results can be found in [7,8,44]. …”
Section: Topological Solitons In Crystalline Pementioning
confidence: 99%
“…It is now clear that acoustic solitons may contribute to the most efficient mechanism of energy transfer in such processes as heat conduction and breakdown of solids [1][2][3][4]. Topological solitons serve as models of structural defects in polymer crystals, and their mobility ensures the possibility of such processes as plastic deformation [5], relaxation [6], and premelting [7,8]. Crystal structure defects are described in a natural way using the concept of topological solitons [9,10], and soliton mobility defines a specific 'soliton' contribution to the thermodynamics and kinetics of polymer crystals.…”
mentioning
confidence: 99%
“…At the macroscopic scale, propagation of solitary waves has been observed in a variety of nonlinear mechanical systems, including chains of elastic beads [9][10][11][12][13][14], tensegrity structures [15], origami chains [16], wrinkled and creased helicoids [17] and flexible architected solids [18][19][20][21]. Moreover, it has been found that even at the molecular scale solitons affect the properties of a variety of onedimensional structures, including macromolecular crystals [22], polymer chains [23][24][25][26], DNA and protein molecules [27][28][29][30]. Since detailed experimental investigation of the dynamic behavior of these microscopic systems is limited by their scale, the identification of macroscale structures capable of describing their response is of particular interest as those offer opportunities to visualize the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%